Magnetic properties and existence of charge ordering state in La1-xCaxMn)3 system - Vu, Mai Thanh; Nguyen, Sinh Huy; Nguyen, Tuan Anh; Do, Minh Hong (VNU Journal of Science: Mathematics - Physics; Vol 20 No 3AP, 2017)
abstracts